Effect of Mirror Therapy on Dexterity and Hand Grasp in the Children Aged 9-14 Years Old with Hemiplegic Cerebral Palsy - Narimani, Akbar; Kalantari, Minoo; Dalvand, Hamid; Tabatabaee, Seyed mehdi (Iranian Journal of Child Neurology, 2019)
Abstract Objective Mirror therapy using visual feedback is one of the non-invasive methods along with other commonly used rehabilitation treatments for neurological patients whose therapeutic effects on the affected upper limb of children with hemiplegic cerebral palsy (CP) have also been studied. The aim of this study was to examine the effect of mirror therapy on improving the dexterity and grasp of children with hemiplegic CP. Materials and Methods In this single blind clinical trial, 30 children with hemiplegic CP in rehabilitation centers and special exceptional schools in Tabriz, Iran were randomly divided into two equal intervention (n=15) and control groups (n=15) in 2017. The children of the intervention group were under the mirror therapy for 6 weeks. Occupational therapy exercises were done routinely for both groups. The grasp with dynamometer and dexterity with box and block was measured. Data were analyzed by t-test and paired t-test. Results The results showed that the mean scores of the two groups in dexterity were significantly different after the intervention (P=0.008). However, there was no significant difference between the two groups in grasp (P>0.05). Discussion and Conclusion Mirror therapy in hemiplegic children is useful in improving the dexterity but not in improving of the grasp